Developing and using an applet to enrich students' concept image of rational polynomials. (8th April 2015) - Mason, John
Abstract : This article draws on extensive experience working with secondary and tertiary teachers and educators using an applet to display rational polynomials (up to degree 7 in numerator and denominator), as support for the challenge to deduce as much as possible about the graph from the graphs of the numerator and the denominator. Pedagogical and design aspects of this work are described.